Identifying the Potential Yield of Soybean Genotype in Tidal Land Type C - Gatut Wahyu Anggoro Susanto; Pratanti Haksiwi Putri (Biosaintifika: Journal of Biology & Biology Education, 2019)
Identification of soybean genotypes including potential yield character is a base to understand soybean growth, development, and productivity on potential lands. The purpose of this research is to determine the potential yield of soybean genotype in tidal land type C and their supporting components. Four soybean genotypes and two comparative varieties Anjasmoro and Lawit (adaptive tidal land) were tested on tidal land type C at four locations (three locations in Jambi Province and one location in South Kalimantan Province), July 2017. The research was conducted using a randomized design for each location and repeated four times. The plot size was 12 m2, spacing row 40 cm x 15 cm, two plants for each hole. GH_KR_13, GH_GR_1 andÂ  GH_GR_5 productivity equal with Lawit, the adaptive variety for tidal land type C. While, Anjasmoro showed more than 2.20 t/ha in seeds productivity, 54 filled pod for each plant, with large size of seeds (15.84 gram/100 seeds). Anjasmoro had higher seed productivity than all of genotypes including Lawit. Anjasmoro with itâ€™s potential yield and productivity, can become farmer preferences and deserve to be developed in tidal land type C.Â